Analisis Faktor yang Berhubungan dengan Kejadian Berat Badan Lahir Rendah di Rumah Sakit Kabupaten Lahat - Marya Lely Fetriana; Siti Aisyah; Satra Yunola (Jurnal Kesehatan Saelmakers PERDANA, 2023)
World Health Organization (WHO), prevalence the low birth weight globally is 15.2%. This number shows that around 20 million babies in each year born with low birth weight and 96.5% of them happened in developing countries. The prevalence of low birth weight largest regionally found in South Asian which is 28%, Africa Sub-Sahara 13%, and Latin America 9%. The method used in this study was analytic survey with cross sectional approach. The statistical test was chi-square test. The population of this study was new born babies at DKT Lahat Hospital, Lahat District 2020 which was estimated to be 644 respondents and the sample was 86 respondents. The univariate analysis showed that of 89 respondents studied, there was 22 respondents (25.6%) experienced low baby birth weight, whose with preterm gestational age was 36 respondents (41.9%), whose with anemia was 33 respondents (38.4%), and whose with risky body mass index was 21 respondents (24.4%). The result showed that there was significant relationship between gestational age and low birth weight p value 0.002 < ? = 0,05, there was significant relationship between anemia and low birth weight p value = 0.010 < ? = 0.05, and there was significant relationship between body mass index and low birth weight p value = 0.018 < ? = 0.05. The results of this study are expected to give good and correct midwifery care as an effort to prevent the low birth weight on new born babies